In vivo mutations of calmodulin: a mutant Paramecium with altered ion current regulation has an isoleucine-to-threonine change at residue 136 and an altered methylation state at lysine residue 115. - Lukas, T J (1989)
The Paramecium tetraurelia mutants termed pantophobiacs have altered behavior due to perturbed calcium activation of ion channel activity. The calmodulin from pantophobiac A1 (pntA1) was shown in previous studies to have a single amino acid change at residue 101 that is selective in its effects on activity. This change has no effect on posttranslational modifications. However, the calmodulin from the phenotypically related mutant pantophobiac A2 (pntA2) has a threonine residue at position 136, in the fourth calcium-binding domain, instead of an isoleucine or valine like all other calmodulins. This region of the calmodulin structure is within 4 A of a complementary hydrophobic structure in the third calcium-binding domain, raising the possibility of a perturbation of interdomain interactions in the pntA2 mutant. This possibility is supported by the heterogenous methylation state of lysine-115 in the pntA2 calmodulin. This lysine residue, located in the peptide connecting calcium-binding domains three and four, is fully trimethylated in the wild-type and pntA1 calmodulins. The functional selectivity of these structural changes is demonstrated by the conservation of calmodulin activator activity with a calmodulin-regulated protein kinase that has been used as a standard of comparison. Overall, these results indicate the degree to which the calmodulin can be mutated in vivo without being lethal to the organism, and they provide genetic evidence suggesting that the post-translational methylation state of residue 115 requires the appropriate conformation in addition to the local amino acid sequence.